THE ORGANIZATIONAL CULTURE OF NON-FRANCHISE LOCAL COFFEE SHOP AS A FORM OF SOCIAL ENTREPRENEURSHIP FOR MILENIALS - Fikri, Aldinel (Universitas Indonesia Membangun (Inaba), 2022)
The increasing number of non-franchise local coffee shops is a good sign for the social entrepreneurship sector. Their endeavor in opening jobs opportunity and improving social welfare are highly respected. During the Covid-19 pandemic, various non-franchise local coffee shops tried to maintain their business sustainability. Knowing the organizational culture could be one of them. In this study, the Organizational culture of non-franchise local coffee shops has measured by the Organization Culture Inventory (OCI) instrument, which involved 43 millennial employees and three owners of seven MSMEs of local non-franchise coffee shops in Bandung, West Java. The results indicate that generally, non-franchise local coffee shops in Bandung has dominated by the Constructive dimension which consists of the following aspects: Humanistic/Encouraging = 82.3%; Affiliative = 83.5%; Achievement = 79.9% and Self-Actualizing = 75.1%. The statement indicates that the various non-franchise coffee shops support each employee to interact with each other, both among employees and the customers as well. In completing their tasks, they prioritize a mutual assistance approach that somehow could support employees' enthusiasm and self-actualization at work.